Answer:
<u>-</u><u>5</u><u>g</u><u>(</u><u>4</u><u>)</u><u> </u><u>-</u><u> </u><u>1</u><u> </u><u>is</u><u> </u><u>9</u>
Step-by-step explanation:
![g(x) = 1 - \frac{3}{4} x](https://tex.z-dn.net/?f=g%28x%29%20%3D%201%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20x)
when x is 4:
![g(4) = 1 - \frac{3}{4} \times 4 \\ = 1 - 3 \\ = - 2](https://tex.z-dn.net/?f=g%284%29%20%3D%201%20-%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%5Ctimes%204%20%5C%5C%20%20%3D%201%20-%203%20%5C%5C%20%20%3D%20%20-%202)
therefore:
![- 5g(4) - 1 = - 5( - 2) - 1 \\ = 10 - 1 \\ = 9](https://tex.z-dn.net/?f=%20-%205g%284%29%20-%201%20%3D%20%20-%205%28%20-%202%29%20-%201%20%5C%5C%20%20%3D%2010%20-%201%20%5C%5C%20%20%3D%209)
I think the answer is A but I am not sure. I think you would take the opposite of the y axis.
Hi There!
<span>t < –5 and t may be a negative number!</span>
Answer:
x=23
Step-by-step explanation:
A and D are equal to eachother so you write the equation (x-4)=19. To solve all you have to do is add 4 to each side and you will get the answer of x=23
Answer: D
You get the same answer from doing both!